Antenatal care as a risk factor for caesarean section: a case study in Brazil - Márcia Regina Cangiani Fabbro; Monika Wernet; Nayara Girardi Baraldi; Jamile Claro de Castro Bussadori; Natália Rejane Salim; Bernardino Geraldo Alves Souto; Andréa dos Reis Fermiano (BMC, 2022)
Abstract Background Antenatal care is an important tool to prevent complications and decrease the incidence of maternal and antenatal morbidity and mortality. In Brazil, quality, access, and coverage of antenatal care are described as insufficient. Consequently, high rates of caesarean section, congenital morbidities such as syphilis, maternal and early neonatal mortality occur, as well as obstetric violence and dissatisfaction with healthcare. It is important to reflect on health disparities in antenatal care. This study aimed to carry out a critical analysis of antenatal care in one city of São Paulo state in Brazil. Methods A case study was performed, structured in a descriptive cross-sectional epidemiological study and two qualitative studies. Data for the epidemiological study was obtained from the Informatics Department of the Unified Health System (DATASUS) of Brazil, which was processed in the Epi-info v software 7.2. and treated descriptively and by the Mantel-Haenszel or Fisher's exact tests. Qualitative data was collected through semi-structured interviews with 30 pregnant women and 8 nurses in the primary healthcare service of one city in São Paulo. The qualitative data analysis was based on thematic content analysis. Results The data revealed a limited quality of antenatal care. More than six antenatal visits increased the probability of a caesarean section by 47% and babies born vaginally had a lower Apgar score. There was little participation of nurses in antenatal care and women described it as "a quick medical appointment", limited by protocols, based on procedures and insufficient in dialogue. Antenatal care appeared to be fragmented and permeated by challenges that involve the need for change in management, performance, and ongoing training of professionals, as well as in the guarantee of women's rights. Conclusions Caesarean section was statistically related to the number of antenatal care visits. Interactions between professionals and pregnant women were poor and resulted in dissatisfaction. There is an urgent need to connect health indicators with the findings from professionals and women's experiences to improve the quality of antenatal care.